استخدام وسائل التواصل الاجتماعي على العلاقات الاجتماعية وعلاقتها بالأفكـار اللاعقلانيــة لـدى طلبة مرحلة التعليم ما بعد الأساسي بسلطنة عمان - رواحي، جمعة محمد حمد (Kulliyah of Education, International Islamic University Malaysia, 2021)
The study aims to explore the impact of the use of social media on social relations and its relationship to irrational ideas, as it used a descriptive multi-design (quantitative, qualitative) multi-sequential explanatory approach to achieve the goals of the study and answer its questions. The study population consists of post-basic education students in the schools of Ad-Dakhiliya Governorate in the Sultanate of Oman for the year 2018/2019, amounting to (11942) male and female students, applied to them the quantitative study tool. The quantitative sample was chosen by way of stratified random sampling by 10% of the study population, which is estimated at (1232) male and female students. Moreover, the qualitative study sample was chosen by means of a random cluster method, estimated at 60 male and female students, by ten students for each group, with three groups for males, and three groups for females. In the statistical treatment, the study used arithmetic means and standard deviations to calculate the scores of social media use. Scores for irrational thoughts, and a T-test to calculate differences for the sex variable; And the (One Way Anova) test of variance to calculate the variance of the variable of household income. The study concluded several results including that the degree of students students use of social media is within the average limits, and the majority of students use it less than three hours per day. The study results also showed that the WhatsApp software is the most used at a rate of 88.31%. The study results revealed that there is a high percentage of students who have smartphones, estimated by 91.8%. The results of the study also revealed that the consequences of the use of social media on social relations were moderate. Moreover, the results indicated a positive direct correlation between the use of social media and irrational thoughts, and that the prevalence of irrational ideas among students was at a moderate degree. Also, the study revealed statistically significant differences in the use of social media and the prevalence of irrational ideas attributed to gender in favor of males. They also indicated that there are no statistically significant differences in the use of social media due to the income variable, while there were significant differences in irrational ideas attributable to the income variable, in favor of low-income levels.